Spatial and Temporal Aggregation in Racial Profiling - Dragan Ilić (Swiss Journal of Economics and Statistics, 2013)
In the last decade, models of rational choice have chimed into the discussion on racial profiling, the use of race in stop and search decisions of the police. The models describe the behavior of motorists and the police and provide empirical tests to assess the question whether the police exhibit racial animus. However, existing studies have neglected the effect of spatial and temporal aggregation of the data on the application of the tests. Using data from the Florida Highway Patrol, this paper shows that regional subsets disclose policing behavior which deviates substantially from the aggregate. Broad conclusions on the absence or presence of racial prejudice are thus at risk of being unfounded. In addition, the disaggregated analysis suggests that the empirical tests implied by the rational choice models are not applicable to all observed regions. The results call for a cautious application of the tests and the interpretation of their conclusions.
Keywords: J71; K42; 330; Racial Profiling; Crime; Police; Rational Choice; Outcome Test; Aggregation